In-Home Deployments - Brush, A.J.; Meyers, Brian; Scott, James (Studying and Designing Technology for Domestic Life: Lessons from Home, 2014)
In-home deployments can be used to study current behavior patterns, or to evaluate prototype systems. Compared to other options such as lab studies, interviews or surveys, in-home deployments offer unparalleled realism due to the in-situ nature of the deployment as part of the participants’ normal lives. However, in-home deployments require careful planning and considerable effort. This chapter will help you plan and successfully execute home deployment studies by sharing insights drawn from our combined experience running many different studies in the home, and by using the PreHeat prototype deployment [Scott et al. 2011] as a concrete example. Among the lessons we highlight are the importance of carefully considering the minimum viable prototype to build for your deployment, the value of remote monitoring so you can catch problems, and the importance of flexibility and robustness in deployed systems to cope with unexpected issues in the home environment. We hope by discussing the challenges we have faced and the lessons we have learned that others will be able to more easily conduct in-home deployments and gather the rich and informative data they provide. Our experiences have also led us to develop and open source two platforms that strive to reduce the engineering effort required for deployments: .NET Gadgeteer, a prototyping platform for custom devices, and Lab of Things, an SDK that provides features such as remote monitoring and update for home deployments.